2021
DOI: 10.1021/acs.jpclett.1c02354
|View full text |Cite
|
Sign up to set email alerts
|

Metal Halide Scaffolded Assemblies of Organic Molecules with Enhanced Emission and Room Temperature Phosphorescence

Abstract: Ionically bonded organic metal halide hybrids have emerged as versatile multicomponent material systems exhibiting unique and useful properties. The unlimited combinations of organic cations and metal halides lead to the tremendous structural diversity of this class of materials, which could unlock many undiscovered properties of both organic cations and metal halides. Here we report the synthesis and characterization of a series benzoquinolinium (BZQ) metal halides with a general formula (BZQ)­Pb2X5 (X = Cl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Moreover, contrary to their organic salt counterparts, 2D HOIPs exhibit stronger and more persistent phosphorescence. [ 10 ] Recently, Hu et al showed that the mixed cation HOIPs can achieve a phosphorescence yield of 11.2% by suppressing nonradiative recombination. [ 11 ] Yang et al reported an efficient and yellow RTP generated by the 1,8‐naphthalimide in Cl‐based 2D HOIPs with a quantum yield of 56.1% and a lifetime of 35 ms. [ 12 ] The latter performance is comparable to the state‐of‐the‐art yellow RTP materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, contrary to their organic salt counterparts, 2D HOIPs exhibit stronger and more persistent phosphorescence. [ 10 ] Recently, Hu et al showed that the mixed cation HOIPs can achieve a phosphorescence yield of 11.2% by suppressing nonradiative recombination. [ 11 ] Yang et al reported an efficient and yellow RTP generated by the 1,8‐naphthalimide in Cl‐based 2D HOIPs with a quantum yield of 56.1% and a lifetime of 35 ms. [ 12 ] The latter performance is comparable to the state‐of‐the‐art yellow RTP materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has led to structures including higher coordination numbers, some exhibiting notable optical properties including enhanced photoluminescence. For example, hybrids with the benzoquinolinium cation were formed with eight-coordinate Pb­(II) centers . A bimetallic Pb–Mn hybrid halide showed multiple Pb­(II) sites with coordination numbers of 6–8 .…”
Section: Introductionmentioning
confidence: 99%
“…To design high-performance 2D perovskite URTP material with type I quantum-well-like structure and rigid 2D layered gallery to cooperatively stabilize the triplet excitons of organic cations, both organic and inorganic parts should be carefully considered. PbCl 2 with a high-lying energy level and the insulating property is chosen to construct the inorganic layers because of its high potential in confining excitons to organic layers by forming type I quantum-well-like structure, directing the organic molecule patterning for enhanced URTP, and suppressing the oxygen penetration to reduce triplet exciton quenching. , Also, lead (Pb) and different halogens (Cl or Br) with tunable heavy atomic effects may promote SOC significantly when serving as metal-halide units . As to the organic part, the widely used PEA cation in 2D perovskites is modified by methoxyl because the electron-donating methoxyl can significantly shift the molecular energy levels, promote ISC to populate the triplet excited state, and suppress the nonradiative decays through the formation of hydrogen-bonding interactions .…”
Section: Resultsmentioning
confidence: 99%